HUBUNGAN TINGKAT KECEMASAN DENGAN TINGKAT PENGETAHUAN PASIEN YANG AKAN DILAKUKAN SECTION CAESAREAN METODE ERACS DI RUMAH SAKIT HERMINA PADANG - Anita Darmayanti,; Aryaldy Zulkarnaini,; Desi Aliefia,; Dian Budianti,; Rezy Saputra, (Nusantara Hasana Journal, 2023)
Pregnancy always has risks that may cause mortality, morbidity and disability in the mother or baby. The Maternal Mortality Rate (MMR) is an indicator to determine the success of maternal health efforts. Various efforts have been made to reduce maternal mortality, one of which is by conducting regular antenatal checks to check the condition of the mother and fetus on a regular basis to reduce the severity of obstetric complications and increase awareness of the danger signs of pregnancy. More knowledge and understanding is needed. Increasing knowledge of the danger signs of pregnancy is considered a strategy that encourages the use of skilled care during pregnancy. This study aims to describe the knowledge of pregnant women about danger signs of pregnancy at the Lubuk Buaya Padang Health Center in 2022-2023. The scope of this research is the field of obstetric medicine. The research was conducted in August 2022 - January 2023. The type of research is descriptive. The affordable population in this study were pregnant women who came to the Lubuk Buaya Padang Health Center in 2022. The type of data was taken, namely primary data of 55 samples using a simple random sampling technique using a questionnaire instrument that had been tested for validity and reliability. It was found that the highest age group for pregnant women was the non-risk age group (20-35 years) with 49 people (89.1%). The highest education for pregnant women was in the high school group with 35 people (63.6%). The most pregnant women in the non-working group were 40 people (72.7%). The highest number of gravid pregnant women was the multigravid group with 35 people (63.6%). The knowledge of pregnant women about danger signs of pregnancy was mostly in the group of pregnant women with good knowledge of 37 people (67.3%). Based on the identification of the description of the knowledge of pregnant women about the danger signs of pregnancy at the Lubuk Buaya Health Center for the period August 2022 - January 2023, it can be concluded that the knowledge of pregnant women about the danger signs of pregnancy is mostly good.